Higher Education Fields of Study and the Use of Transferable Skills at Work: An Analysis Using Data from the Programme for the International Assessment of Adult Competencies (PIAAC) in Canada - Christine E. B. Mishra; David Walters; Evan D. G. Fraser; Daniel Gillis; Shoshanah Jacobs (Trends in Higher Education)
Given the rapidly changing job market in Canada and globally, there have been increasing calls to address the transferable skills gap between higher education graduates and the skills needed for the many new and changing jobs across the labour market. To investigate which fields of study in higher education in Canada produce graduates who go on to use more transferable skills on the job, we created an index of transferable skills use at work from several background questionnaire variables available in the Programme for the International Assessment of Adult Competencies (PIAAC) in Canada survey. A series of four least squares linear regression models were used to examine the impacts of variables such as field of study and occupation type on this transferable skills index. Teacher training and education programs were found to have the highest scores on the transferable skills index, suggesting that these programs (and other professional programs) should be considered as a source of inspiration for how all programs can promote transferable skill development in their students. We also found a connection between transferable skill use and management roles within the workplace, suggesting that transferable skills are important factors in promotion to management roles.